2010
DOI: 10.1242/jcs.064055
|View full text |Cite
|
Sign up to set email alerts
|

Kidins220/ARMS regulates Rac1-dependent neurite outgrowth by direct interaction with the RhoGEF Trio

Abstract: SummaryNeurite extension depends on extracellular signals that lead to changes in gene expression and rearrangement of the actin cytoskeleton. A factor that might orchestrate these signalling pathways with cytoskeletal elements is the integral membrane protein Kidins220/ARMS, a downstream target of neurotrophins. Here, we identified Trio, a RhoGEF for Rac1, RhoG and RhoA, which is involved in neurite outgrowth and axon guidance, as a binding partner of Kidins220. This interaction is direct and occurs between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 56 publications
1
74
0
Order By: Relevance
“…Recombinant proteins corresponding to Trio fragments 1 to 8 were expressed in E. coli BL21(DE3) cells, except for fragment 2, which was expressed in E. coli Rosetta, and were purified as described previously (41). Briefly, 1 liter of log-phase bacteria was induced with 1 mM isopropylthiogalactopyranoside (IPTG) and shaken overnight at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant proteins corresponding to Trio fragments 1 to 8 were expressed in E. coli BL21(DE3) cells, except for fragment 2, which was expressed in E. coli Rosetta, and were purified as described previously (41). Briefly, 1 liter of log-phase bacteria was induced with 1 mM isopropylthiogalactopyranoside (IPTG) and shaken overnight at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…A crucial aspect of Rac1 and Cdc42 activity is their activationdependent accumulation at discrete sites in the plasma membrane. At these sites, they colocalize with other proteins, including their GEFs, for example TRIO (triple functional domain protein), VAV, DOCK1 (dedicator of cytokinesis 1) and PREX1 (for phosphatidylinositol 3,4,5-trisphosphate-dependent Rac exchanger 1) (see, among others, Premkumar et al, 2010;Neubrand et al, 2010;Tolias et al, 2011;Citi et al, 2011). As expected, downregulation of these GEFs results in the inhibition of Rac1-and/or Cdc42-dependent processes (Côté and Vuori, 2007).…”
Section: Rho Gtpases -Mechanisms Of Action and Localizationmentioning
confidence: 55%
“…ARMS has been directly linked to NGF-mediated signaling (Arévalo et al, 2006(Arévalo et al, , 2004Neubrand et al, 2010) and NGF elicits regulated secretion (Canossa et al, 1997;Kruttgen et al, 1998). To investigate the role of ARMS, we utilized PC12 cells because they respond to NGF (Greene and Tischler, 1976) and are a model widely used to study secretion (Westerink and Ewing, 2008).…”
Section: Ngf Stimulates Secretion Of Hgh In Pc12 Cellsmentioning
confidence: 99%
“…In order to determine how ARMS and synembryn-B could modulate secretion, we took into account that NGF treatment leads to Rac1 activation (Nusser et al, 2002;Yamaguchi et al, 2001) and that ARMS has been shown to modulate Rac1 activation through the GEF Trio (Neubrand et al, 2010). Because Ric-8 regulates Trio through Gαq (Williams et al, 2007), we assessed whether ARMS and synembryn-B regulated Rac1 activity in response to NGF.…”
Section: Rac1 Regulates Ngf-stimulated Secretion Downstream Of Arms Amentioning
confidence: 99%
See 1 more Smart Citation